A Review on Manufacturing and Characterization Oro-Dispersible Tablet - Ali, Hiba Muhammed Suza; Al-Khedairy, Eman Bekir (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oro-dispersible tablets have emerged as an important advancement in oral solid dosage forms due to their ability to rapidly disintegrate in the oral cavity without water. Specific Background: Their development is driven by patient demand for convenient medication, especially for pediatric, geriatric, and dysphagic populations who experience difficulty swallowing conventional tablets. Knowledge Gap: Despite wide application, comprehensive evaluation of fabrication methods, excipient functions, and characterization parameters across traditional and modern manufacturing technologies remains limited. Aims: This review analyzes the terminology, advantages, limitations, commonly used excipients, manufacturing techniques, and critical quality assessments of ODTs. Results: The study highlights diverse preparation approaches including lyophilization, sublimation, wet granulation, direct compression, mass extrusion, and emerging three-dimensional printing, each offering unique benefits related to disintegration behavior, mechanical strength, and processing efficiency. Novelty: The article synthesizes conventional pharmaceutics knowledge with recent technological innovations such as selective laser sintering and fused deposition modeling, demonstrating how modern techniques enhance precision and personalization of dosage forms. Implications: Findings underscore that optimized excipient selection and manufacturing strategies are fundamental to ensuring rapid disintegration, mechanical stability, acceptable taste, and enhanced bioavailability, reinforcing ODTs as a growing platform for patient-centered drug delivery.Highlight : Oro-dispersible tablets dissolve rapidly on the tongue, improving convenience for patients with swallowing difficulties. Formulation uses specific excipients—especially superdisintegrants—to achieve fast disintegration and effective performance. Can be produced using various traditional and modern manufacturing methods such as direct compression, sublimation, and 3D printing. Keywords : Disintegration, Oral solid dosage form, Oro-dispersible tablet, Patients’ compliance, Manufacturing techniques